2017
DOI: 10.17511/ijpr.2017.i01.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of procalcitonin versus c-reactive protein in the diagnosis of sepsis in children below 16 years-a single centre observational study

Abstract: Introduction: Given the limitation of non-specific nature of signs, symptoms and physical examination in diagnosing sepsis; especially in young children, a diagnostic marker that will aid in an early diagnosis is needed. Procalcitonin satisfies most of the criteria for smart biomarker of sepsis. The present study is done to compare procalcitonin (PCT) with C-reactive protein (CRP) as a diagnostic marker of sepsis in children. Materials & Methods: A prospective observational study was done in the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…4,28 A few authors have shown PCT to be a more sensitive and specific marker for sepsis in children with burns than CRP. [29][30][31] However, both these parameters require enzyme backed assays for estimation, which are costly and may not be available in remote settings.…”
Section: Discussionmentioning
confidence: 99%
“…4,28 A few authors have shown PCT to be a more sensitive and specific marker for sepsis in children with burns than CRP. [29][30][31] However, both these parameters require enzyme backed assays for estimation, which are costly and may not be available in remote settings.…”
Section: Discussionmentioning
confidence: 99%